2015
DOI: 10.1111/jpr.12080
|View full text |Cite
|
Sign up to set email alerts
|

Online monitoring of the social presence effects in a two‐person‐like driving video game using near‐infrared spectroscopy

Abstract: We examined how a friend's presence affects a performer's prefrontal activation in daily‐life activities using two wireless portable near‐infrared spectroscopy (NIRS) devices. Participants played a driving video game either solely in the single group or with a friend in the paired group. The two groups (single and paired) were subdivided according to their game proficiency (low and high). The NIRS data demonstrated a significant interaction of group by proficiency. Low‐proficiency players in the paired group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Therefore, reported changes in brain activity due to gaming were rather heterogeneous. Some studies reported a global decrease of oxy-Hb over frontal brain areas during gaming [23][24][25][26][27]. However, differences in task complexity, cognitive load, expertise, or subjective user experience during playing may have added to these different brain activation patterns [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reported changes in brain activity due to gaming were rather heterogeneous. Some studies reported a global decrease of oxy-Hb over frontal brain areas during gaming [23][24][25][26][27]. However, differences in task complexity, cognitive load, expertise, or subjective user experience during playing may have added to these different brain activation patterns [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%